Meningkatkan Keterampilan Berpikir Kreatif Melalui Model Pembelajaran Context-Based Learning (CBL) Pada Materi Dinamika Gerak - Hairiyah, Hairiyah; Suartini, Kinkin; Al Farizi, Taufiq (Jayapangus Press, 2024)
One of the troubles in Indonesian training is that the system of tutorial development remains not substantial and is abstract and even a way from actual existence, making it tough to train college students' creative wondering abilties. This study targets to enhance innovative questioning talents using the context-based learning (CBL) studying model on motion dynamics fabric. There are several articles associated with these studies for analysis. The sample for this research was 64 students taken from 2 classes, namely class XI K and XI L among 6 class XI at SMAN 3 Pandeglang. The methodology employed for data analysis to ascertain an increase in creative thinking skills in students is the N-gain test. Based on the N-gain analysis, the findings indicated an improvement in creative thinking skills using the context-based learning (CBL) learning model on Motion Dynamics material. This was obtained derived from the outcomes of statistical calculations which indicated the presence of increase in the value of N-gain in the class undergoing the experiment by 0.84 in the high category, while in the control class the N-gain value was only 0.39 falling within the moderate category. Therefore, learning using the context-based learning model is recommended to be employed to enhance the creative thinking abilities of students, especially in contextually related materials such as Motion Dynamics material.